Introduction to the Special Issue: THE TRIANON PEACE TREATY, POST-WAR SETTLEMENT AND THE ANGLO-SAXON WORLD: 100th Anniversary of the Treaty of Trianon - Cora, Zoltán (AMERICANA E-journal of American Studies in Hungary, 2020)
Introduction to the Special Issue: THE TRIANON PEACE TREATY, POST-WAR SETTLEMENT AND THE ANGLO-SAXON WORLD: 100th Anniversary of the Treaty of Trianon